Surface‐Supported Robust 2D Lanthanide‐Carboxylate Coordination Networks. Issue 47 (2nd November 2015) - Urgel, José I.; Cirera, Borja; Wang, Yang; Auwärter, Willi; Otero, Roberto; Gallego, José M.; Alcamí, Manuel; Klyatskaya, Svetlana; Ruben, Mario; Martín, Fernando; Miranda, Rodolfo; Ecija, David; et al.
Abstract : Lanthanide‐based metal–organic compounds and architectures are promising systems for sensing, heterogeneous catalysis, photoluminescence, and magnetism. Herein, the fabrication of interfacial 2D lanthanide‐carboxylate networks is introduced. This study combines low‐ and variable‐temperature scanning tunneling microscopy (STM) and X‐ray photoemission spectroscopy (XPS) experiments, and density functional theory (DFT) calculations addressing their design and electronic properties. The bonding of ditopic linear linkers to Gd centers on a Cu(111) surface gives rise to extended nanoporous grids, comprising mononuclear nodes featuring eightfold lateral coordination. XPS and DFT elucidate the nature of the bond, indicating ionic characteristics, which is also manifest in appreciable thermal stability. This study introduces a new generation of robust low‐dimensional metallosupramolecular systems incorporating the functionalities of the f‐block elements. Abstract : On‐surface assembly of robust 2D lanthanide‐carboxylate coordination networks . The codeposition of TDA linker species and Gd on Cu(111) results in the formation of reticular networks, based on Gd–carboxylate interactions featuring a unique eightfold mononuclear node, which are thermally stable up to 400 K. X‐ray photoemission spectroscopy experiments and density functional theory calculations reveal the predominant ionic nature of the bond.